(3GdEaUGM Yf eYGfi GdUMGMs - (3jMji Hf (B((3gHjQI Hf(B) (3eMeO Hf gHjQI GdPgdj GdTjHGfqj, CHh GdeXaQ, Yhf GdOjf,J (B560 (3g` s ((3YHO Gdhdi Hf MSf Hf YHO Gdhdi GdOQhi GdbhUi GdTGaYi s)
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf CeG HYO , aEfi cfJ TOjO GdYRe Edi QDjI cJGH jTJed Ydi CMGOjK QShd Gddg Udi Gddg Ydjg hSde s
(3BNQgG (B:s
(3hcPdc jSJMH Cf jMfc GdWad HGdJeQ Cf hLO Ch GdYSd jbGd UHi eMfhc heMfc hjbGd MfcJg HGdJNaja CjVkG hjSJMH Cf jOYh ddWad HGdHQcI BNQ GdeLdO hGdMeO ddg hMOg s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B175 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B228s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdeMehOjI (B- (3HGdeOjfI GdefhQI (B((3MOjK (B3) s
Keywords: (3GdMOjK h GdeUWdMs